A Relevance Theory Analysis in Metaphor: (Analisis Teori Relevans dalam Metafora) (Jurnal Bahasa, 2018)
This research was conducted to detect metaphors in poems and analysing these to reveal their true meanings. This is a qualitative piece of research employing the Relevance Theory, which is a linguistics-based theory by Sperber and Wilson (1986) from the discipline of pragmatics. This theory underlines three main concepts that comprise the role of context, cognitive effects and processing efforts. This theory suggests that all these three concepts are vital and should be taken into consideration in interpretation of meanings. Five lines of metaphors from five poems written by Usman Awang (UA) were chosen as data. Text analysis was then carried out in stages, based on the three main concepts mentioned. Besides these three main concepts and the five main metaphors explored, the researcher also utilised the existence of other figurative expressions, non-figurative expressions and other lexical items to further strengthen interpretation. It was found that the application of Relevance Theory was helpful in understanding the actual meaning. The study also reveals that the existence of the various figurative expressions alongside the five main data explored, the non-figurative expressions and other lexical items are also helpful in decoding meanings. These are reasoned out by readers/listeners ad-hoc to understand the meaning of lines and lexical item. Relevance theory is found to facilitate interpretation of meaning with greater validity.Keywords: metaphor, relevance theory, linguistics, pragmatics, figurative languages.